Evidence for Size-Selective Predation by Antarctic Humpback Whales - Cade, David E.; Kahane-Rapport, Shirel R.; Wallis, Ben; Goldbogen, Jeremy A.; Friedlaender, Ari S. (Frontiers in Marine Science, 2022)
Animals aggregate around resource hotspots, but what makes one resource more appealing than another can be difficult to determine. In March 2020 the Antarctic fjord Charlotte Bay included >5× as many humpback whales as neighboring Wilhelmina Bay, a site previously known for super aggregations of whales and their prey, Antarctic krill. We used suction-cup attached bio-logging tags and active acoustic prey mapping to test the hypothesis that whale abundance in Charlotte Bay would be associated with higher prey biomass density, and that whale foraging effort would be concentrated in regions of Charlotte Bay with the highest biomass. Here we show, however, that patch size and krill length at the depth of foraging were more likely predictors of foraging effort than biomass. Tagged whales spent >80% of the night foraging, and whales in both bays demonstrated similar nighttime feeding rates (48.1 ± 4.0 vs. 50.8 ± 16.4 lunges/h). However, whales in Charlotte Bay foraged for 58% of their daylight hours, compared to 22% in Wilhelmina Bay, utilizing deep (280–450 m) foraging dives in addition to surface feeding strategies like bubble-netting. Selective foraging on larger krill by humpback whales has not been previously established, but suggests that whales may be sensitive to differences in individual prey quality. The utilization of disparate foraging strategies in different parts of the water column allows humpback whales to target the most desirable parts of their foraging environments.